2018
DOI: 10.4236/jamp.2018.64064
|View full text |Cite
|
Sign up to set email alerts
|

Where Do We Stand on High Heels in 2018? An Audit

Abstract: We present an audit of public awareness, freedom of choice and health behavior change relating to high heel wear subsequent to a major public awareness campaign in the summer of 2017. Substantial reductions in workplace high heel wear were found, whereby increasingly those who wear high heels regularly at work have freely chosen to do so, although certain issues of social expectations remain in certain sectors. Largely, freedom of choice has greatly increased in workplaces in line with increased public and emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Wearing high-heeled shoes is a common practice among women in the Western world, despite the fact that it involves various health risks [ 5 , 6 , 7 ]. Although Dilley, Hockey, Robinson, and Sherlock [ 8 ] clearly demonstrated peer and workplace pressure on women to wear high-heeled shoes, a study conducted in the United Kingdom found that 67% of the female participants regularly wore high heels at work by their own choice, whereas only 13% of them reported that they merely complied with a requirement or dress code by doing so [ 9 ]. At the same time, Barnish, Morgan, and Barnish [ 10 ] found in a meta-analysis that wearing high heels might provide certain psychosexual benefits for women.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Wearing high-heeled shoes is a common practice among women in the Western world, despite the fact that it involves various health risks [ 5 , 6 , 7 ]. Although Dilley, Hockey, Robinson, and Sherlock [ 8 ] clearly demonstrated peer and workplace pressure on women to wear high-heeled shoes, a study conducted in the United Kingdom found that 67% of the female participants regularly wore high heels at work by their own choice, whereas only 13% of them reported that they merely complied with a requirement or dress code by doing so [ 9 ]. At the same time, Barnish, Morgan, and Barnish [ 10 ] found in a meta-analysis that wearing high heels might provide certain psychosexual benefits for women.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The author concluded that visually increased leg length might promote intrasexual rivalry between women for access to the opposite sex through the enhancement of sexual attractiveness. Reynolds et al [ 9 ] found that 98% of the 932 female participants reported willingness to wear high heels at parties or clubs. Women’s preference for wearing high-heeled shoes may be explained by its potential to enhance the wearer’s attractive physical features by changing her body posture.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Thus, where it was logical to do so, we framed questions in terms of the PDR-relevant effects of clothing that could be experienced by any gender rather than specific articles of clothing or fashion accessories. We did retain reference to shoes as a specific article of clothing based on the substantial amount of literature on the discomfort associated with high heels (e.g., Jeffreys, 2015 ; Parmentier, 2016 ; Reynolds et al, 2018 ) and the fact that all genders regularly wear shoes of some sort. Two questions asked about shoes outright but again focused on the PDR effects of shoes (shoes that cause pain/blisters and shoes that limit the time one can comfortably stand) rather than a specific type of shoe.…”
Section: Methodsmentioning
confidence: 99%